2019
DOI: 10.11646/zootaxa.4700.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Myiocephalus Marshall (Hymenoptera: Braconidae: Euphorinae), with description of one new species

Abstract: The Palaearctic species of Myiocephalus Marshall, 1898 (Braconidae, Euphorinae) are revised and a new species (M. zwakhalsi sp. n.) from Austria is described and illustrated. A key to the Palaearctic species is provided. Myiocephalus niger Fischer, 1957, is a new record for China and the Nearctic Myiocephalus laticeps (Provancher, 1886) is re-instated as valid species. A lectotype is designated for Aphidius hedini Fahringer, 1929.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,185 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Remarks. The new species runs in the key by Tan et al (2019) to M. zwakhalsi, but differs from it as follows: 1) vein cu-a of fore wing distinctly longer than 1-CU1 and vertical (ca. as long as 1-CU1 and oblique in M. zwakhalsi); 2) prepectal carina present medio-ventrally (absent medio-ventrally); 3) scapus yellow dorsally (dark brown); 4) first metasomal tergite of ♀ slender in lateral view (robust); 5) hind coxa rugulose-striate (finely striate); 6) setose part of ovipositor sheath ca.…”
Section: Taxonomic Accountsmentioning
confidence: 92%
See 4 more Smart Citations
“…Remarks. The new species runs in the key by Tan et al (2019) to M. zwakhalsi, but differs from it as follows: 1) vein cu-a of fore wing distinctly longer than 1-CU1 and vertical (ca. as long as 1-CU1 and oblique in M. zwakhalsi); 2) prepectal carina present medio-ventrally (absent medio-ventrally); 3) scapus yellow dorsally (dark brown); 4) first metasomal tergite of ♀ slender in lateral view (robust); 5) hind coxa rugulose-striate (finely striate); 6) setose part of ovipositor sheath ca.…”
Section: Taxonomic Accountsmentioning
confidence: 92%
“…The first author examined the collections applying the key of Tan et al (2019) and discovered a new species than it was confirmed by second author and is described below.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations